Protection and Status of Children Born Outside of Marriage: A Fiqh Perspective Of Indonesia And Brunei Darussalam - Khairuddin, Khairuddin; Rini, Etika; Purwaningsih, Titin; Sugianto, Heri; Ismail, Habib; Lubis, Rahmad (STAINI Press, 2025)
This study discusses the problem of protection and the position of children out of wedlock in Indonesia and Brunei Darussalam, especially in the context of differences and similarities in legal policies between the two countries based on the perspective of Islamic jurisprudence. Children out of wedlock often face serious legal and social challenges, such as limited recognition of biological fathers, inheritance rights, and inherent social stigma. This research uses a qualitative approach with the library research method. Data was collected from a variety of relevant secondary sources, including scientific journals, law and jurisprudence books, as well as official documents such as national laws and regulations and Constitutional Court rulings in Indonesia. The analysis was carried out comparatively by examining the policy of protection of children out of wedlock in Indonesia and Brunei Darussalam from the perspective of positive law and Islamic jurisprudence. The results of the study show that Indonesia has adopted a relatively more inclusive policy in providing protection for the rights of children out of wedlock through legislative reforms and Constitutional Court rulings. However, its implementation is still hampered by social factors such as societal stigma and low legal awareness. Meanwhile, Brunei Darussalam, which strictly applies Sharia law, shows a tendency towards more limited protection, especially related to the recognition of inheritance rights and the civil status of children out of wedlock. This article concludes that the differences in legal approaches in the two countries reflect the dynamics of Islamic jurisprudence interpretation in the context of modern countries. Both Indonesia and Brunei need to improve public legal literacy and make efforts to reduce social stigma to ensure more effective and equitable protection for children out of wedlock.